Using Ce to modify inclusion in spring steel - Wang Q.; Wang L.J.; Liu Y.Q.; Chou K.C. (Journal of Mining and Metallurgy. Section B: Metallurgy)
The effect of rare earth metals addition on the Al2O3 inclusions in spring steel used in fastener of high speed railway was investigated by metallographic examination, SEM-EDS and composition analysis. To deform those harmful inclusions to improve material performance，the evolution process of Al2O3 inclusions was investigated through the surface and line scanning. Ce metal modifying Al2O3 is a stepwise reduction process based on a formation of ring shape Ce-riched band around the Al2O3 inclusions during reaction process. Through experiment and thermodynamic calculation, an evolvement rule about Al2O3 inclusions change after Ce addition is obtained, i.e. Al2O3→Ce2O3-Al2O3→Ce2O2S. Changing the inclusions from Al2O3 to rare earth inclusions could improve the resistance to pitting corrosion based on potentiodynamic anodic polarization test.